The effect of education on prevention of urinary tract infection - Ghiasvandian Sh (Iran University of Medical Sciences, 1998)
A quasi experimental study evaluated the effects of education on prevention of urinary tract infection of women in two groups of patients with immobility. A total of 100 patients (50 case, 50control) that qualified to be the subjects of this study were selected.   The study focused on variables such as: teaching, urinary tract in. action in immobility. Thus two to shot data was gathered.   A questionnaire, check-list, urinanalysis, and urine culture were completed during this study. The data are presented in 30 tables. The descriptive measures were further manipulated by X2 and Fisher and Cochran tests and inference was made according to correlations.   A highly significant difference (95%) was noticed among variables such as unspecial antibiotic, blood group, daily drinks and infection paraclinic signs and bacterial adherence with calcium in the urine. A significant difference was not noticed between the nurse, health behavior such as menstrual protection, urination, and diet with urinary tract infection after 2 weeks of immobility in the two groups.   In addition, information of subjects in case group increased after teaching and highly a significant difference was noticed in the two groups.   Another significant finding was pyuria, proteinuria and crystal uria in 48 hours and 2 weeks after teaching in the two groups.   Based on these findings recommendations were made, as well as suggestions for further studies. These findings may serve as bases for educating the public and planning programs to prevent urinary tract infections in women.